PARA ALÉM DO DISCURSO POLÍTICO A INTERDISCURSIVIDADE EM UM ANÚNCIO PUBLICITÁRIO DE CERVEJA (Muitas Vozes, 2022)
The present work investigates, under the theoretical focus of French Discourse Analysis, in its articulation with the perspective of discursive genres, an advertisement for Rio Carioca beer, whose meaning effects refer to cases of corruption in Brazilian politics. With the methodological principle of an empirical research, of a documentary and interpretative nature, we analyze the due announcement, observing how the publicity text, when choosing political themes approached by the humor bias, insofar as it establishes a dialogue with national politics, makes it possible in their regularities effects of truth on their historical conditions of existence. If it is important for us to develop in our students their perception of discourse, as a socio-historical-cultural process, studying the advertisement is to reveal the link it establishes with public life, insofar as it politicizes its statements and breaks paradigms in the media field.